Relevansi Wakaf Ahli dalam Membangun Ketahanan Keluarga - Suraiya, Ratna; Jauhari, Nashrun (STAINI Press, 2022)
Family waqf is oriented towards realizing family welfare in a sustainable manner, as the realization of the purposes of Shari'a Hifdz al-Nasal. The condition of families in Indonesia after the Covid-19 pandemic has experienced many resilience problems, so rescue efforts are needed. Using normative legal research methods, qualitatively, this research finds a synergy between family waqf and the concept of family resilience which is recognized in Indonesia, through five components: (1) legality and family integrity foundations, (2) physical resilience, (3) economic resilience ; (4) psychological social resilience (5) socio-cultural resilience. Useful research shows strategic steps in efforts to build families in Indonesia so that they have sustainable resilience